Team roles: Their relationships to character strengths and job satisfaction. Issue 2 (4th March 2018) - Ruch, Willibald; Gander, Fabian; Platt, Tracey; Hofmann, Jennifer
Abstract: Well-functioning teamwork has frequently been linked to increased work satisfaction and performance. However, there is a paucity of research on the different types of roles in teams. Recently, a new model of role behavior in teams was proposed (comprising seven such team roles: Idea creator, information gatherer, decision-maker, implementer, influencer, energizer, and relationship manager), but an assessment instrument was lacking so far. The present study describes the construction of an instrument for the assessment of these roles in two samples ( N = 291 and 274) and examines their relationships with character strengths and job satisfaction. Results show that the team roles are positively related to job satisfaction and most character strengths. The findings support the important role of character strengths in work-related settings and lay ground for further studies on team roles.